Autotrophic Fixed-Film Systems Treating High Strength Ammonia Wastewater - Aqeel, Hussain; Liss, Steven N. (Frontiers in Microbiology, 2020)
The aim of the study was enrichment of nitrifying bacteria and to investigate the potential of autotrophic fixed-film and hybrid bioreactors to treat high strength ammonia wastewater (up to 1,000 mg N/L). Two types of fixed-film systems [moving bed biofilm reactor (MBBR) and BioCordTM] in two different configurations [sequencing batch reactor (SBR) and a continuous stirred tank reactor (CSTR)] were operated for 306 days. The laboratory-scale bioreactors were seeded with activated sludge from a municipal wastewater treatment plant and fed synthetic wastewater with no organics. Strategies for acclimation included biomass reseeding (during bioreactor start-up), and gradual increase in the influent ammonia concentration [from 130 to 1,000 mg N/L (10% every 5 days)]. Stable ammonia removal was observed up to 750 mg N/L from 45 to 145 days in the MBBR SBR (94–100%) and CSTR (72–100%), and BioCordTM SBR (96–100%) and CSTR (92–100%). Ammonia removal declined to 87% ± 6, in all bioreactors treating 1,000 mg N/L (on day 185). Following long-term operation at 1,000 mg N/L (on day 306), ammonia removal was 93–94% in both the MBBR SBR and BioCordTM CSTR; whereas, ammonia removal was relatively lower in MBBR CSTR (20–35%) and BioCordTM SBR (45–54%). Acclimation to increasing concentrations of ammonia led to the enrichment of nitrifying (Nitrosomonas, Nitrospira, and Nitrobacter) and denitrifying (Comamonas, OLB8, and Rhodanobacter) bacteria [16S rRNA gene sequencing (Illumina)] in all bioreactors. In the hybrid bioreactor, the nitrifying and denitrifying bacteria were relatively more abundant in flocs and biofilms, respectively. The presence of dead cells (in biofilms) suggests that in the absence of an organic substrate, endogenous decay is a likely contributor of nutrients for denitrifying bacteria. The nitrite accumulation and abundance of denitrifying bacteria indicate partial denitrification in fixed-film bioreactors operated under limited carbon conditions. Further studies are required to assess the contribution of organic material produced in autotrophic biofilms (by endogenous decay and soluble microbial products) to the overall treatment process. Furthermore, the possibility of sustaining autotrophic nitrogen in high strength waste-streams in the presence of organic substrates warrants further investigation.